An analytical approach to the effects of zakat on poverty rates in Algeria - djefafla, abdelaali; boukra, kamilia (Journal of Research in Finance and Accounting, 2022)
This study aimed to highlight the impact of zakat proceeds in Algeria on poverty in the country during the period 2003/2021. The study concluded, according to the condition of $1.25, that the impact of the proceeds of the Zakat Fund on poverty levels in Algeria is relatively weak due to the lack of its outcome and its focus on a wide category of society, but it remains impossible to measure the impact of Zakat money due to the absence of a compulsory zakat system because Algeria depends on the capital tax